2015
DOI: 10.1371/journal.pone.0132434
|View full text |Cite
|
Sign up to set email alerts
|

Two Virus-Induced MicroRNAs Known Only from Teleost Fishes Are Orthologues of MicroRNAs Involved in Cell Cycle Control in Humans

Abstract: MicroRNAs (miRNAs) are ~22 base pair-long non-coding RNAs which regulate gene expression in the cytoplasm of eukaryotic cells by binding to specific target regions in mRNAs to mediate transcriptional blocking or mRNA cleavage. Through their fundamental roles in cellular pathways, gene regulation mediated by miRNAs has been shown to be involved in almost all biological phenomena, including development, metabolism, cell cycle, tumor formation, and host-pathogen interactions. To address the latter in a primitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 96 publications
3
17
0
Order By: Relevance
“…Similar motifs were identified in the promoter region of the miRNA-462/731 cluster in rainbow trout (Schyth et al, 2015) and Atlantic salmon , and the potential conservation among species suggests that these motifs may be associated with immune responsiveness of the miRNA-462/731 cluster. These miRNAs also showed a time-dependent upregulation in response to injection of IFNG-expressing plasmids (Bela-ong et al, 2015).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Similar motifs were identified in the promoter region of the miRNA-462/731 cluster in rainbow trout (Schyth et al, 2015) and Atlantic salmon , and the potential conservation among species suggests that these motifs may be associated with immune responsiveness of the miRNA-462/731 cluster. These miRNAs also showed a time-dependent upregulation in response to injection of IFNG-expressing plasmids (Bela-ong et al, 2015).…”
Section: Discussionmentioning
confidence: 54%
“…In Atlantic cod (Andreassen et al, 2016), these miRNAs were found to be clustered in the genome and potentially co-transcribed as in other teleost species, i.e. rainbow trout (Oncorhynchus mykiss) (Schyth et al, 2015), Atlantic salmon and zebrafish (Danio rerio) (Thatcher et al, 2008). These two teleost-specific miRNAs have been reported as virus-and bacteria-responsive in several teleost species .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, microRNAs are not the near-perfect markers for which they are sometimes taken. In some cases they have diverged beyond the point where homology is readily recognized (Schyth et al, 2015). Several clades, in particular Urochordata (Fu et al, 2008) and Platyhelminthes (Fromm et al, 2013), have undergone a massive restructuring of their microRNA repertoire.…”
Section: Micrornasmentioning
confidence: 99%
“…DALR is an anticodon binding domain of tRNA synthetase (arginyl/cysteinyl), made of α helices. In human, this domain-containing protein DALRD3 interacts with protein WDR6 (WD Repeat Domain 6) and C3orf60 (chromosome 3 open reading frame 60), involved in autophagy and protein assembly, respectively (Grinchuk et al, 2010;Schyth et al, 2015). DALR_1 domain detected in pollen might have role in manipulating gene expression.…”
Section: Ligase and Synthetasesmentioning
confidence: 99%